P54 Framework for Delivery of Elective Orthopaedic Surgery in the United Kingdom Following the COVID-19 Pandemic. (8th April 2021) - Sharkey, Samantha; Narang, Karamveer; Pacheco, Ricardo; Anthony, Christopher; Narang, Karamveer
Abstract: Background: As we enter a second wave of the COVID-19 pandemic, a framework for safe provision of elective orthopaedic surgery must be developed in order to restore and maintain activity. The aim of this study was to explore patient attitudes to surgery and theatre efficiency in light of the COVID-19 pandemic and assess a potential framework for the delivery of such services. Methods: Prospectively collected data on theatre timings and procedures completed per session used to assess theatre efficiency using 40 patients from June 2019 and 85 patients from June 2020. Information on patient compliance with 14-day household isolation and attitudes to surgery were collected prospectively over a 7-week period using a questionnaire (37 patients included). Follow up data was collected via telephone consultation a minimum of 2 weeks after discharge. Results: Significant reduction in the number of points per session (p = 0.02) with a mean of 3.19 in 2019 and 2.42 in 2020. Only 18 of 31 patients were compliant with pre-operative isolation with individual failures accounting for 4 of 13 and failures by household members accounting for 9. Impact on COVID-19 and precautions on patient anxiety was mixed. No patients required symptomatic COVID-19 swab. Interpretation: With the restrictions of COVID-19 there are significant problems with theatre efficiency, in effect losing an operation a list. Furthermore, compliance with pre-operative isolation was poor. Additional strategies will be required to re-instate an effective elective orthopaedic service, especially as the nation heads into a second wave.